IDENTIFIKASI DAN MITIGASI ERROR DENGAN METODE SHERPA DAN HEART UNTUK MENINGKATKAN KINERJA K3 DI DIVISI KENDARAAN KHUSUS PT PINDAD - Citra Pantja Gelora, Amanda
PT PINDAD is a manufacturing company engaged in the defense and security sector. PT PINDAD produces munitions, weapons, and combat vehicles to support the defense and security sector. This role requires high productivity with good health and safety levels. Data on work accidents in the Special Vehicles Division shows that in 2023, work accidents increased after two years of achieving zero accidents. Based on work accident data in five years, the cause of work accidents is dominated by human error. One of the solutions is to map the potential errors that can occur and design mitigation related to these errors. The Fabrication Preparation Sub-Department is the section with the most high-risk work being the object of the research. This study used the Systematic Human Error Reduction and Prediction (SHERPA) and Human Error Assessment and Reduction Technique (HEART) methods. The selection considers the result of each method. The SHERPA method analyzes the types of human errors that occur along with the risk level of the consequences of each activity. At the same time, the HEART method quantifies human error probability (HEP). The highest HEP value with a moderate to high consequence risk value is a priority in solution design. The results of this research indicate that there are high-risk activities, including the activity of raising and lowering the roll on a rolling machine, the activity of rotating the roll on a rolling machine, the activity of writing a program on a CNC bending machine, and the bending process activity on a conventional bending machine. These results indicate the design of a solution by modifying the control panel to be more informative, using reminder sensors for safety, and other supporting facilities, such as supporting tools for the roll machine and discussion tables and chairs for translating technical drawings. The design results show the prevention of human error by considering the type of human error that occurs, its causes, and the needs of operators as users. This design helps companies increase productivity by preventing human error and improving worker safety..